Deactivation of ZSM-5 during catalytic fast pyrolysis of biomass - Stanton, Alexander R., author; Reardon, Kenneth, advisor; Iisa, Kristiina, advisor; Dandy, David, committee member; Marchese, Anthony, committee member; Smith, Gordon, committee member (Colorado State University. Libraries, 2018)
To view the abstract, please see the full text of the document.
Keywords: biomass; deactivation; ZSM-5; catalytic fast pyrolysis; biofuel; pyrolysis